Metabolic reprogramming of oncogene-addicted cancer cells to OXPHOS as a mechanism of drug resistance - Hirpara, J.; Eu, J.; Tan, J.; Wong, A.; Clement, M.; Kong, L.; Ohi, N.; Tsunoda, T.; Qu, J.; Goh, B.; Pervaiz, Shazib (Elsevier BV, 2019)
The ability to selectively eradicate oncogene-addicted tumors while reducing systemic toxicity has endeared targeted therapies as a treatment strategy. Nevertheless, development of acquired resistance limits the benefits and durability of such a regime. Here we report evidence of enhanced reliance on mitochondrial oxidative phosphorylation (OXPHOS) in oncogene-addicted cancers manifesting acquired resistance to targeted therapies. To that effect, we describe a novel OXPHOS targeting activity of the small molecule compound, OPB-51602 (OPB). Of note, a priori treatment with OPB restored sensitivity to targeted therapies. Furthermore, cancer cells exhibiting stemness markers also showed selective reliance on OXPHOS and enhanced sensitivity to OPB. Importantly, in a subset of patients who developed secondary resistance to EGFR tyrosine kinase inhibitor (TKI), OPB treatment resulted in decrease in metabolic activity and reduction in tumor size. Collectively, we show here a switch to mitochondrial OXPHOS as a key driver of targeted drug resistance in oncogene-addicted cancers. This metabolic vulnerability is exploited by a novel OXPHOS inhibitor, which also shows promise in the clinical setting.